Mindfulness goes mainstream [videorecording (DVD)] : techniques. - Kabat-Zinn, Jon; Kornfield, Jack, 1945-; Tan, Chade-Meng (PBS Distribution, 2017)
The fundamental benefit of mindfulness is that it improves your overall health and well-being. Learn techniques from some of the nation's leading experts, including Jon Kabat-Zinn and Chade-Meng Tan, who will teach you how to focus your attention in a brand new way.